2020
DOI: 10.2196/18690
|View full text |Cite
|
Sign up to set email alerts
|

Notifications to Improve Engagement With an Alcohol Reduction App: Protocol for a Micro-Randomized Trial

Abstract: Background Drink Less is a behavior change app that aims to help users in the general adult population reduce hazardous and harmful alcohol consumption. The app includes a daily push notification, delivered at 11 am, asking users to “Please complete your mood and drinking diaries.” Previous analysis of Drink Less engagement data suggests the current notification strongly influences how users engage with the app in the subsequent hour. To exploit a potential increase of vulnerability of excess drink… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…This project will be the first known implementation of an MRT protocol to optimize a JITAI on the proximal outcome of eating behavior. Across the field of health behavior change, MRTs remain novel; there are several MRTs in the process of optimizing JITAIs in the areas of physical activity [ 85 , 86 ], smoking cessation [ 87 , 88 ], stress management [ 88 ], mood [ 86 ], medication adherence [ 89 ], and substance use [ 90 , 91 ]. A recently completed MRT to increase self-monitoring in a commercial wellness app for lifestyle behaviors found that sending prompts with tailored suggestions (vs tailored feedback) significantly increased the odds of self-monitoring and that the frequency of engagement with the app moderated this effect (eg, as frequency of self-monitoring increased and sending prompts with suggestions reduced the odds of engagement) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…This project will be the first known implementation of an MRT protocol to optimize a JITAI on the proximal outcome of eating behavior. Across the field of health behavior change, MRTs remain novel; there are several MRTs in the process of optimizing JITAIs in the areas of physical activity [ 85 , 86 ], smoking cessation [ 87 , 88 ], stress management [ 88 ], mood [ 86 ], medication adherence [ 89 ], and substance use [ 90 , 91 ]. A recently completed MRT to increase self-monitoring in a commercial wellness app for lifestyle behaviors found that sending prompts with tailored suggestions (vs tailored feedback) significantly increased the odds of self-monitoring and that the frequency of engagement with the app moderated this effect (eg, as frequency of self-monitoring increased and sending prompts with suggestions reduced the odds of engagement) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear whether a different message (e.g. to engage with all the app’s available features) may lead to increased time spent or screens viewed – this is currently explored in a different study, specifically designed to optimise the push notifications in Drink Less [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now our priority to understand the causal effect of the notification on engagement and to consider further optimizing the push notification policy to contextual circumstances of individuals over time to inform the development of a just-in-time adaptive intervention. The MRT aims to inform the development of decision rules to tailor the notification policy to individuals over time, with details found in our protocol [ 65 ].…”
Section: Discussionmentioning
confidence: 99%